ANALYSIS FACTORS OF FISH CONSUMPTION LEVELS AMONG TEENAGERS ON DKI JAKARTA - Azalea Fathin Hasna; Yudi Nurul Ihsan; Atikah Nurhayati; Ine Maulina (Universitas Mataram, 2025)
Nutrional needs in adolescents is closely related to the consumption of animal protein, which one of it is fish consumption. The diverse consumption patterns of teenagers mean that their nutrional intake is not optiomal. DKI Jakarta is a densely populated province that has large fisheries resource potentional. As a coastal area who has Kepulauan Seribu and Teluk Jakarta, Jakarta’s fisheries potential is obtained through the production of fisheries and aquaculture. In this regard, data regarding the level of fish consumption in one area is very necessary. This research aims to determine the level of fish consumption among teenagers in DKI Jakarta as well as knowledge of fish nutrition and the factors that influence the level of fish consumption among teenagers. The analytical method used is multiple linear regression analysis and descriptive analysis using the SPSS (Social Package of Statistics Software) program. The data obtained came from primary data by distributing questionnaires via Google Form which were distributed via social media. The sampling technique used in this research was cluster random sampling. Respondents totaled 360 respondents, each of whom was divided into 60 respondents in 5 municipalities and 1 district. The four factors, namely childhood eating habits, nutritional knowledge, parental income, and consumer preferences have a significant effect on the level of fish consumption among teenagers in DKI Jakarta.